Birth of the dragon [videorecording (DVD)] - Wu, Yunlong, 1977-; Xia, Yu, 1978-; Jin, Xing, 1967- (Universal Pictures Home Entertainment, 2017)
Set against the backdrop of 1960s San Francisco, this is a modern take on the classic movies that Bruce Lee was known for. It takes its inspiration from the epic and still controversial showdown between an up and coming Bruce Lee and kung fu master Wong Jack Man, a battle that gave birth to a legend.